2005
DOI: 10.1158/0008-5472.can-05-1666
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin E Both Regulates and Is Regulated by Calpain 2, a Protease Associated with Metastatic Breast Cancer Phenotype

Abstract: Overexpression of cyclin E in breast tumors is associated with a poor response to tamoxifen therapy, greater genomic instability, more aggressive behavior, and a poor clinical prognosis. These tumors also express low molecular weight isoforms of cyclin E that are associated with higher kinase activity and increased metastatic potential. In the current study, we show that cyclin E overexpression in MCF7 cells transactivates the expression of calpain 2, leading to proteolysis of cyclin E as well as several known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2008
2008
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 56 publications
3
43
0
Order By: Relevance
“…2A). We previously showed that proteolysis of the calpain substrate focal adhesion kinase (FAK) is a good indicator of calpain activity (22). Calpeptin treatment of R1 cells reduced the levels of LMW-FAK ( Fig.…”
Section: Resultsmentioning
confidence: 97%
“…2A). We previously showed that proteolysis of the calpain substrate focal adhesion kinase (FAK) is a good indicator of calpain activity (22). Calpeptin treatment of R1 cells reduced the levels of LMW-FAK ( Fig.…”
Section: Resultsmentioning
confidence: 97%
“…For example, in Src-transformed cells, FAK is extensively cleaved compared with other adhesion complex proteins (38,39). In addition, human tumors overexpressing cyclin E have been associated with increased proteolysis of FAK (40). By contrast, in myoblasts overexpressing calpastatin, the proteolytic patterns of talin and FAK are unchanged, whereas an accumulation of MARCKS (myristoylated alanine-rich C kinase substrate) has been observed, indicating that calpain may preferentially cleave MARCKS to affect myoblast migration (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…Calpain is often hyperactivated in tumor cells (Carragher et al, 2004;Libertini et al, 2005), where it plays a major role in migration and metastasis due to its ability to cleave cytoskeletal proteins. Interestingly, PP2A negatively regulates calpain in nicotine-stimulated cell migration (Xu and Deng, 2006), in line with its tumor suppressor role.…”
Section: Discussionmentioning
confidence: 99%